Secret mission to the Philippines the story of the "Spyron" and the American-Filipino guerrillas of World War II - Wise, William 1923- (Dutton, 2001)
Describes the unusual World War II command of Chick Parsons who, as leader of the American-Filipino guerrilla movement, lived behind enemy lines, never carried arms or fired a shot, and became one of America's most decorated heroes.